The relative merits of different methods of teaching experimental work in a township secondary school in the Republic of South Africa - Mabuya, Mavis Buyisiwe (My University, 1993)
The purpose of this study to determine which of the methods of teaching experimental work, namely; demonstrations filmed-experiments or illustrating experiments using the chalkboard, is the most effective method of teaching pupils at the secondary school level. Forty-two Standard Eight Physical Science pupils from a township secondary school, registered under the Department of Education and Training and situated on the East Rand served as the subjects for this study. Pupils were divided in to three equivalent groups, each with similar marks in science and each group was exposed to three different teaching methods for three different topics. The pupils wrote a test for each topic after the exposure to one of the methods. The research data were statistically analysed, using non parametric statistics ( viz., the t-test). The analysis of the data indicates that none of the methods was consistently superior to the others.
RESEARCH REPORT SUBMITTED TO THE FACULTY OF SCIENCE, UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG, IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE DEGREE OF MASTER OF SCIENCE.
Keywords: Science -- Study and teaching (Secondary) -- South Africa.; Science -- Experiments -- Study and teaching (Secondary) -- South Africa.; Blacks -- Education -- South Africa.